DAMPAK DARI PRAKTIK CORPORATE GOVERNANCE TERHADAP FIRM VALUE - - Subagyo (JAFFA, 2014)
This study aimed to examine the effect of corporate governance practices (CG) on firm value with Return on Assets as control variable.  Firm value in this study is proxied by market-to-book value ratio. This study measured the CG practices by using institutional ownership, managerial ownership, the proportion of independent board and audit committee. Sample to be used in this study is Financial Sector firm that listed in Indonesia. The result of this research indicates that managerial ownership and audit committee had significant effect on market to book value ratio. Another finding shows that institutional ownership, the proportion of independent board, and the control variable ROA have no significant effect on market to book value ratio.